Elastography Study of Hamstring Behaviors during Passive Stretching - Le Sant, Guillaume (PLoS One, 2015)
INTRODUCTION: The mechanical properties of hamstring muscles are usually inferred from global passive torque/angle relationships, in combination with adjoining tissues crossing the joint investigated. Shear modulus measurement provides an estimate of changes in muscle-tendon stiffness and passive tension. This study aimed to assess the passive individual behavior of each hamstring muscle in different stretching positions using shear wave elastography. METHODS/RESULTS: The muscle shear modulus of each hamstring muscle was measured during a standardized slow passive knee extension (PKE, 80% of maximal range of motion) on eighteen healthy male volunteers. Firstly, we assessed the reliability of the measurements. Results were good for semitendinosus (ST, CV: 8.9%-13.4%), semimembranosus (SM, CV: 10.3%-11.2%) and biceps femoris long-head (BF-lh, CV: 8.6%-13.3%), but not for biceps femoris short-head (BF-sh, CV: 20.3%-44.9%). Secondly, we investigated each reliable muscle in three stretch positions: 70°, 90° and 110° of hip flexion. The results showed different values of shear modulus for the same amount of perceived stretch, with the highest measurements in the high-flexed hip situation. Moreover, individual muscles displayed different values, with values increasing or BF-lh, SM and ST, respectively. The inter-subject variability was 35.3% for ST, 27.4% for SM and 30.2% for BF-lh. CONCLUSION: This study showed that the hip needs to be high-flexed to efficiently tension the hamstrings, and reports a higher muscle-tendon stress tolerance at 110° of hip angle. In addition muscles have different passive behaviors, and future works will clarify if it can be linked with rate of injury.